SEKOLAH ALAM OMAH KEPOMPONG BANJARBARU - Dewi Puspita Sari; Dila Nadya Andini (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The nature school is one of the developing natural environment-based education systems in Indonesia that uses the school's natural environment as a medium of learning, one of which is Banjarbaru City. However, the limited land area results in limited spaces and it also causes the school to limit the number of incoming students and the existing indoor and outdoor spaces are not fully connected to its base as a nature school. Based on this, Omah Kepompong Nature School emphasizes 2 things, namely indoor & outdoor spaces that are connected to nature and space for child learning. The concept of Connecting Nature & Child’s Learning Space formulated based on the biophilic architecture approach is applied through physical and non-physical forms that prioritize attachment to nature, sustainability and comfort so as to create an environment that can provide physical & mental well-being of its users.